Abstracts from international Emergency Medicine journals. Issue 8 (20th July 2016) - Weber, Ellen J
Abstract : Editor's note: EMJ has partnered with the journals of multiple international emergency medicine societies to share from each a highlighted research study, as selected by their editors. This edition will feature two abstracts from each publication.